1975
DOI: 10.1007/bf00510818
|View full text |Cite
|
Sign up to set email alerts
|

Histamine receptors in the vasculature of the rabbit ear

Abstract: Histamine has a dual action on the isolated perfused ear preparation of the rabbit. The amine induced a dose-dependent rise in perfusion pressure when the preparation was perfused with Krebs' solution. This pressor response was reversed to a depressor effect when meypramine was added to the perfusion fluid. This depressor effect of the amine was also dose-related. Metiamide competitively inhibited the depressor effect of histamine. Prior treatment of the ear vessels with metiamide alone caused an increase in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…results in dilatation of the vessels. In most other species investigated, there is a predominance of H2-receptor participation in the vasodilator responses to histamine and a Hl-receptor mediated vasoconstriction in the external carotid vascular bed (Edvinsson & Owman, 1975;Saxena, 1975;Duckworth et al, 1976;Parsons & Owen, 1973;Ercan & Turker, 1975). However, in human temporal arteries only vasodilatation was seen, and this response seemed mainly to be mediated via H2-receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…results in dilatation of the vessels. In most other species investigated, there is a predominance of H2-receptor participation in the vasodilator responses to histamine and a Hl-receptor mediated vasoconstriction in the external carotid vascular bed (Edvinsson & Owman, 1975;Saxena, 1975;Duckworth et al, 1976;Parsons & Owen, 1973;Ercan & Turker, 1975). However, in human temporal arteries only vasodilatation was seen, and this response seemed mainly to be mediated via H2-receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In carotid vascular bed have been studied in man, histamine produces a headache often animals both in vitro and in situ. In the rabbit and associated with increased pulsation in the cat histamine has been found to be a vasotemporal artery, and a rise in blood, and oc-constrictor agent (Furukawa, 1954; Owen, 1973, Ercan & Turker, 1975, Edvinsson & Owman, 1975. This response seems to be a reflection of a balance between a histamine H1-receptor mediated vasoconstriction and a histamine H2-receptor mediated vasodilatation (Glover et al, 1973;Edvinsson & Owman, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, influences of histamine on cat and rat gastric (Guth & Smith, 1978a;Harvey, Owen & Shaw, 1980), rat, rabbit, cat and dog mesenteric (Flynn & Owen, 1975;Angus & Korner, 1977;Pawlik, Tague, Tepperman, Millar & Jacobson, 1977;Guth & Smith, 1978b), rabbit and pig coronary (Coruzzi, Bongrani & Bertaccini, 1979;Hagen & Paegelow, 1980), rabbit renal (Angus & Korner, 1977), rabbit ear (Ercan & Turker, 1975), cat and dog cerebral vasculatures (Edvinsson & Owman, 1975;Toda, 1977;Wahl & Kuschinsky, 1979) and cat and dog blood pressure (Black, Owen & Parsons, 1975) have been described. Some of these authors have postulated from the results of experiments in situ that both H1-and H2-receptors participate in a common response, such as a vasodilatation, an increase in the blood flow and a fall of the blood pressure (Black et al, 1975;Flynn & Owen, 1975;Angus & Korner, 1977;Pawlik etal., 1977;Guth & Smith, 1978a, b;Harvey et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…A dual action o f the amine has been observed in the vasculature o f the isolated perfused kidney (3) and ear (7) o f this species. In addition, it has been shown that histamine induces a biphasic response in the mean arterial pressure of urethane-anesthetized rabbits.…”
mentioning
confidence: 99%